Numerical model for CFRP confined concrete elements subject to monotonic and cyclic loadings - Varma, Rajendra K.; Barros, Joaquim A.O.; Sena-Cruz, José M. (Composites. Part B, Engineering, 2009)
Uniaxial cyclic and monotonic compression tests were carried out on partially and fully wrapped concrete cylinders with Carbon Fibre Reinforced Polymer (CFRP) wet lay-up sheets. The influence of the concrete compressive strength, CFRP stiffness, geometric confinement arrangement and loading type on the compressive behaviour of reinforced concrete column elements of circular cross-section up to their failure was assessed. A uniaxial stress–strain constitutive model is proposed, and the results obtained from the experimental tests were used to calibrate some of the parameters of this model, and to appraise the model performance. This model allows the simulation of reinforced concrete members by using Timoshenko one-dimensional elements, in the context of the finite element method (fibre model). Good agreement was obtained between numerical simulations and experimental results for both monotonic and cyclic loading tests.